2020
DOI: 10.36708/littera_scripta2019/2/12
|View full text |Cite
|
Sign up to set email alerts
|

Considering seasonal fluctuations in equalizing time series by means of artificial neural networks for predicting development of USA and People´s Republic of China trade balance

Abstract: Balance of payments is an accounting identity of each country. The ability to make a qualified and accurate prediction of trade balance of huge world economies such as the USA and the People´s Republic of China economies can have influence on the world´s economy. An enormous expansion and advancement of artificial intelligence offers a possibility to measure and predict also this indicator. The aim of the contribution is to propose a methodology for taking into account the seasonal fluctuations in equalizing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Vrbka has investigated the performance of the artificial intelligence based gross domestic product modelling and forecasting methods for the Eurozone countries and they have concluded that radial basis function based functions has the best performance for the modelling of the gross domestic products [51]. In another study, Chuku et al have studied the comparison of the gross domestic product growth modelling performance of artificial neural networks and the Box-Jenkins approach for African economies and they…”
Section: Modelling the Gross Domestic Product And The Per Capita Inco...mentioning
confidence: 99%
“…Vrbka has investigated the performance of the artificial intelligence based gross domestic product modelling and forecasting methods for the Eurozone countries and they have concluded that radial basis function based functions has the best performance for the modelling of the gross domestic products [51]. In another study, Chuku et al have studied the comparison of the gross domestic product growth modelling performance of artificial neural networks and the Box-Jenkins approach for African economies and they…”
Section: Modelling the Gross Domestic Product And The Per Capita Inco...mentioning
confidence: 99%
“…As previously mentioned, according to Vrbka et al (2019), international trade is considered to be crucial for economic growth, the essence of which consists of the exchange of goods, services, and capital across national borders. Horak and Machova (2019) stated that, in contrast to trade at the domestic level, the implementation of this trade type is a very complex process.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Forecasting time series accurately is a critical challenge with significant implications, especially in predicting economic growth. Gross Domestic Product (GDP) is one of the most important economic indicators for comparing and evaluating the economic performance of countries and regions, and economists are constantly in search of better ways to predict GDP [1,2].…”
Section: Introductionmentioning
confidence: 99%